(untitled) (FAVE Sección Ciencias Veterinarias, 2022)
Ovarian cysts can be seen relatively frequently in female cats, and their incidence may increase with the age of the females. They are thin-walled ovarian structures with liquid content inside, which can be single or multiple and can be unilateral or bilateral. Follicular cysts usually originate from mature or atretic follicles in which ovulation does not occur; the majority secrete estrogens and prevent the reestablishment of folliculogenesis, causing prolonged estrus and infertility. A mixed short hair breed queen, 6 months of age and weighing 2 kg, was examined at the Animal Reproduction Service of the Faculty of Veterinary Sciences of the National University of La Plata for doing a permanent control of reproduction by ovariectomy. The cat was found clinically healthy, on physical examination, showing signs of heat and vaginal cytology. An ovarian cyst with a diameter of 0.5 cm was found in the left ovary during the oophorectomy. During the surgery were removed the right ovary and the left ovary with the cyst and, then the queen became in anestrus.